Pandangan Dosen PTKI Di Madura Terhadap Formula Ijtihad Muhammad Bin Abdul Wahhab - A. Ghufran Ferdiant; Mohammad Bashri Asyari (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2020)
Lecturers as academics, educators, researchers and actors of community service are seen as groups of people who have a deeper ability to research and objectively examine the products of contemporary renewal thinking according to their competence and have the opportunity to disseminate them to the wider community. sufficient access in influencing the public's understanding and views of issues of contemporary renewal thinking, especially those that are still considered controversial, such as the views of ijtihad Muhammad Ibn Abd. Wahhab. This article used descriptive field research to examined the views of PTKAI lecturers in Madura to find out their knowledge of the Ijtihad Muhammad bin Abdul Wahhab formula with the title "The Views of PTKI Lecturers in Madura Against Ijtihad Muhammad Ibn Abd al-Wahhab's Formula" with two problem formulations: How the views of PTKI lecturers in Madura on the Ijtihad Muhammad bin Abdul Wahhab formula and what factors are behind the PTKI lecturers' view of the Ijtihad Muhammad bin Abdul Wahhab’s formula.